2021
DOI: 10.1002/dneu.22802
|View full text |Cite
|
Sign up to set email alerts
|

Adult‐like neural representation of species‐specific songs in the auditory forebrain of zebra finch nestlings

Abstract: Encoding of conspecific signals during development can reinforce species barriers as well as set the stage for learning and production of species‐typical vocalizations. In altricial songbirds, the development of the auditory system is not complete at hatching, so it is unknown the degree to which recently hatched young can process auditory signals like birdsong. We measured in vivo extracellular responses to song stimuli in a zebra finch (Taeniopygia guttata) secondary auditory forebrain region, the caudomedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 70 publications
(124 reference statements)
0
6
0
Order By: Relevance
“…Later, mainly in zebra finches, the neural responses were compared across ages to investigate how such neural selectivity develops. Consistent with the sensitivity to own-species song at a behavioral level, electrophysiological recordings ( Stripling et al, 2001 ; Schroeder and Remage-Healey, 2021 ) and immunohistochemical assay ( Stripling et al, 2001 ; Bailey and Wade, 2003 , Bailey and Wade, 2005 ) showed that some neurons in the NCM selectively respond to conspecific song over heterospecific song either at a single-cell level or at a population level. These results indicated that the selectivity is already present at the age of 20 days post hatch, which is said to be the beginning of the sensory learning in this species ( Roper and Zann, 2006 ).…”
Section: Juvenile Song Preferencementioning
confidence: 55%
“…Later, mainly in zebra finches, the neural responses were compared across ages to investigate how such neural selectivity develops. Consistent with the sensitivity to own-species song at a behavioral level, electrophysiological recordings ( Stripling et al, 2001 ; Schroeder and Remage-Healey, 2021 ) and immunohistochemical assay ( Stripling et al, 2001 ; Bailey and Wade, 2003 , Bailey and Wade, 2005 ) showed that some neurons in the NCM selectively respond to conspecific song over heterospecific song either at a single-cell level or at a population level. These results indicated that the selectivity is already present at the age of 20 days post hatch, which is said to be the beginning of the sensory learning in this species ( Roper and Zann, 2006 ).…”
Section: Juvenile Song Preferencementioning
confidence: 55%
“…CR birds also have the opportunity for vocal and visual interactions with individuals outside their family, and there may be more diffuse effects of social density on brain development 57 . It also remains to be seen to what extent the effects we observed are the result of an early sensitive period 58 or more recent plasticity 28 . Future work could begin to address these questions by controlling the timing and statistics of the acoustical background presented via loudspeaker to PR clutches.…”
Section: Discussionmentioning
confidence: 90%
“…However, the potential significance of transcriptional characteristics in auditory areas for the learning outcomes observed in the F 1 hybrids and species-specific learning capacities should not be overlooked. Although a certain number of NCM neurons exhibit varying neural activities in response to conspecific and heterospecific songs ( 51 , 53 , 65 ), only specific subsets of these neurons may play a role in shaping the memory of a song model to be learned ( 52 ). Sampling from multiple auditory regions, including field L (a primary cortical auditory region) and the caudomedial mesopallium (another higher auditory region), could be useful to examine whether some observed differences in song learning capacity are due to variations in the auditory system of F 1 hybrids.…”
Section: Discussionmentioning
confidence: 99%